IDENTIFICATION OF NON-INVASIVE BIOMARKERS FOR EARLY DETECTION OF OVARIAN CANCER - Haruto Takahashi; Kaito Tanaka; Luis Santos (Yayasan Adra Karima Hubbi, 2025)
Ovarian cancer is one of the most lethal gynecologic malignancies due to late diagnosis. Early detection is critical for improving survival rates, yet current screening methods are inadequate. To identify and validate non-invasive biomarkers for the early detection of ovarian cancer, focusing on improving diagnostic accuracy and patient outcomes. This study utilized proteomic and genomic approaches, including mass spectrometry for protein profiling and next-generation sequencing for analyzing cfDNA and miRNAs. Blood samples from patients with early-stage ovarian cancer, healthy controls, and individuals with benign conditions were analyzed. The combination of CA-125 and HE4 biomarkers significantly increased sensitivity (85%) and specificity (90%) for early detection of ovarian cancer compared to CA-125 alone. Proteomic analysis identified significant differences in protein profiles between cancer patients and healthy controls. Genomic analysis revealed specific mutations in cfDNA associated with ovarian cancer. The study demonstrates that a combination of CA-125 and HE4, along with multi-omic approaches, can enhance the early detection of ovarian cancer, providing a basis for the development of more accurate diagnostic tests. Further clinical trials are necessary to validate these findings.